PENDIDIKAN ISLAM DI INDONESIA PADA MASA AWAL: SEBUAH PERJALANAN SEJARAH - Niswah, Choirun; Maharani, Fitria; Amallia, Nuria; Adison, Fahima Ad Dini; Andini, Try (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT This article explores the historical development of Islamic education in Indonesia during the early stages of Islam's arrival in the archipelago. The Islamization process occurred peacefully through trade, preaching, politics, marriage, and education. Institutions such as mosques, suraus, prayer houses, and pesantren served as key centers of Islamic learning that blended with local culture. Using a qualitative approach and library research method, this study traces the dynamics of pre-colonial Islamic educational systems and institutions. The researcher began by searching for primary and secondary sources through databases such as Google Scholar, Garuda, DOAJ, and SINTA using specific keywords. Next, 20 of the most relevant sources were selected. The collected data were then analyzed using a descriptive-analytical approach to examine the development of Islamic education in its social and historical context. The findings indicate that Islamic education played a central role in shaping religious and social identity. Despite challenges such as limited infrastructure and colonial pressure, early Islamic education systems endured and adapted, ultimately becoming a foundational pillar of Indonesia’s national education system today. ABSTRAK Artikel ini mengkaji sejarah perkembangan pendidikan Islam di Indonesia pada masa awal masuknya Islam ke Nusantara. Proses Islamisasi berlangsung secara damai melalui jalur perdagangan, dakwah, politik, pernikahan, dan pendidikan. Lembaga-lembaga seperti masjid, surau, langgar, dan pesantren menjadi pusat utama pendidikan Islam yang menyatu dengan budaya lokal. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka untuk menelusuri dinamika lembaga dan sistem pendidikan Islam pra-kolonial. Penelitian dimulai dengan menelusuri sumber-sumber primer dan sekunder melalui database seperti Google Scholar, Garuda, DOAJ, dan SINTA menggunakan kata kunci tertentu. Selanjutnya, dipilih 20 sumber yang paling relevan. Data yang terkumpul kemudian dianalisis secara deskriptif-analitis untuk mengkaji perkembangan pendidikan Islam dalam konteks sosial dan historis. Hasil kajian menunjukkan bahwa pendidikan Islam memiliki peran sentral dalam pembentukan identitas keagamaan dan sosial masyarakat. Meskipun menghadapi berbagai tantangan seperti keterbatasan infrastruktur dan tekanan kolonial, sistem pendidikan Islam awal mampu bertahan dan beradaptasi hingga menjadi fondasi penting dalam sistem pendidikan nasional saat ini.